Starch Wars—New Episodes of the Saga. Changes in Regulations on Hydroxyethyl Starch in the European Union - Adamik, Katja-Nicole; Yozova, Ivayla D. (Frontiers in Veterinary Science, 2019)
After a safety review of hydroxyethyl starch (HES) solutions in 2013, restrictions on the use of HES were introduced in the European Union (EU) to reduce the risk of kidney injury and death in certain patient populations. Similar restrictions were introduced by the Food and Drug Administration in the United States and other countries. In October 2017, a second safety review of HES solutions was triggered by the European pharmacovigilance authorities based on a request by the Swedish Medical Products Agency to completely suspend HES. After several meetings and repeated evaluations, the recommendation to ban HES was ultimately not endorsed by the responsible committee; however, there was a vote for more restricted access to the drug and rigorous monitoring of policy adherence. This review delineates developments in the European pharmacovigilance risk assessment of HES solutions between 2013 and 2018. In addition, the divergent experts' opinions and the controversy surrounding this official assessment are described. A brief overview on HES-related veterinary literature as well as alternatives to HES is presented. As the new decisions might influence the availability of HES products for veterinary patients, potential alternatives to HES solutions, such as gelatin, dextran, and albumin solutions are briefly discussed.